Comparison of the soft tissue thickness of the chin in individuals with different patterns of facial growth in lateral cephalic radiographs. - Farez Guichay, Diana Paola (2021)
Objective: To compare the soft tissue thickness of the chin in individuals with different patterns of facial growth on lateral cephalic radiographs of the digital skull in individuals between 18 and 45 years of age. Material and Methods: a correlational study was carried out evaluating 160 lateral radiographs using a 13.3-inch screen using AutoCAD 2020 software obtained from a radiological center in the city of Cuenca, in the period 2019. It was divided into four groups according to the pattern of facial growth (SN / G-Gn): Low, Medium Low, Medium High and High and the thickness of the soft tissues of the chin was measured sagittally at the Pogonion, Gnation and Menton level of the bone structures at their respective points in soft tissues. The Spearman Rho correlation was used to evaluate the means of the thickness of the soft tissues of the chin and facial pattern, for the comparison between groups the Tuckey post-hoc test was used, with a confidence level of 95% (p<0,05) Results: Statistically significant differences were found between women at the Gnation level, it showed a value p=0,041, the thickness was greater in the low facial pattern and decreases as the skeletal pattern increases (Rho Spearman=-0,271). Significant differences according to sexual dimorphism at the Menton level (p=0,049) and there were no significant differences according to age. Conclusion: As women present a vertical facial pattern, the Gnation thickness is thinner, which implies that by vertically modifying the hard tissues of the jaw, the soft tissues can be affected.